Preparation method of silane coupling agent modified nano ZSM-5 mixed matrix membrane
By blending 3-aminopropyltriethoxysilane modified nano ZSM-5 with Pebax-1657 to prepare a mixed matrix membrane, the problem of insufficient permeability and selectivity of the existing CO2/N2 gas separation membrane is solved, and efficient gas separation performance and economical preparation cost are achieved.
Patent Information
- Application Number
- CN202411864677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing CO2/N2 gas separation membranes have insufficient permeability and selectivity, and the preparation cost is high.
NanoZSM-5 was modified with 3-aminopropyltriethoxysilane as a silane coupling agent by blending method, and mixed matrix membranes were prepared with Pebax-1657 as a matrix.
The permeability of CO2 and the selectivity of CO2/N2 are significantly improved, the preparation cost is reduced, and the mechanical and thermal stability of the membrane is improved.
Smart Images

Figure CN119499895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas separation materials, in particular to a method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane. Background Art
[0002] In order to meet the needs of industrial production, the burning of a large amount of fossil fuels has led to a far-excessive amount of CO2 in the atmosphere, resulting in a series of events such as global warming and glacier melting. According to the Energy Agency, in 2023, global energy-related carbon dioxide emissions will increase by 1.1%, an increase of 410 million tons, reaching a historical high of 37.4 billion tons. However, as an existing and abundant carbon resource on the earth, CO2 is cheap, non-toxic and renewable, and the rational use and capture of CO2 (CCS) is a sustainable technology with great prospects in energy conservation and emission reduction. At present, the capture methods of CO2 include liquid absorption, adsorption separation, cryogenic distillation and membrane separation. Compared with the other three methods, membrane separation methods are favored by many researchers because of their simple operation, environmental friendliness, low energy consumption and high separation efficiency. Among gas separation membranes, mixed matrix membranes (MMMs) have attracted widespread attention because they combine the advantages of inorganic separation membranes and organic separation membranes and can theoretically break the constraints between permeability and selectivity. Inorganic fillers can not only provide additional gas adsorption sites, but also provide gas diffusion paths. At the same time, the inorganic fillers themselves or by modifying functional groups can interact with the polymer chain, thereby improving the interfacial compatibility and avoiding the generation of defects that are not gas selectivity.
[0003] As a topological aluminosilicate molecular sieve, ZSM-5 is used in many places because of its unique pore structure, adjustable silicon-aluminum ratio, good hydrothermal stability, moderate acidity and high specific surface area. 3-aminopropyltriethoxysilane (APTES) is a common silane coupling agent, and β-cyclodextrin (β-CD) has abundant CO2-philic groups. The modification of ZSM-5 with these two can play a positive role in CO2 separation to a certain extent. The CO2 / N2 separation performance of the mixed matrix membrane prepared by MOFs, HOFs and COFs materials has not reached the ideal state, and its cost is relatively expensive. Therefore, it is a challenging task to study a cheap inorganic material suitable for the field of gas separation, and it will be a new challenge to prepare a mixed matrix membrane with high selectivity and high permeability. Summary of the invention
[0004] In view of the problems existing in the above background technology, the present invention proposes a method for preparing a nano ZSM-5 mixed matrix membrane modified by a silane coupling agent. A method for preparing a mixed matrix membrane for CO2 separation by preparing nano ZSM-5 modified by a silane coupling agent and using it as a filler, and using Pebax-1657 as a matrix. The purpose of the present invention is to introduce a silane coupling agent into nano ZSM-5 by a blending method to prepare nano ZSM-5 modified by a silane coupling agent, which has excellent CO2 adsorption performance, thereby solving the problem of low permeability and selectivity of membrane materials to CO2 / N2, and comparing it with β-cyclodextrin (β-CD) which also has abundant CO2-philic groups, further illustrating the excellent permeability and high CO2 / N2 selectivity of the nano ZSM-5 mixed matrix membrane modified by a silane coupling agent. For this purpose, the present invention provides a method for preparing a nano ZSM-5 mixed matrix membrane modified by a silane coupling agent.
[0005] The technical solution of the present invention:
[0006] A method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane comprises the following steps:
[0007] Step 1, weighing 1-1.5 parts of aluminum isopropoxide and dissolving it in 48-80 parts of an organic template, stirring until the aluminum isopropoxide is fully dissolved, adding 52-65 parts of silicon dioxide, stirring evenly to obtain a slightly wet gel-like mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding deionized water outside the glass bottle mouth in the lining, aging the encapsulated hydrothermal reactor at room temperature for 24-72 hours, transferring the hydrothermal reactor to an electric constant temperature blast drying oven for crystallization treatment to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain dry nano ZSM-5;
[0008] Step 2, add 50-150 parts of toluene to beaker A, add 1-5 parts of 3-aminopropyltriethoxysilane dropwise thereto, and fully dissolve it in the toluene solution; add 50-150 parts of toluene to beaker B, then add 0.05-1 part of nano ZSM-5, and drop the solution in beaker A into beaker B. The speed of this process is 800r / min, and then continue to stir for 2-5 hours, then transfer the mixed solution to a round-bottom flask, add 1-5 drops of ultrapure water, and react in an oil bath at 80-90°C for 12-36 hours. After centrifugal washing and drying with toluene, nano ZSM-5 modified with a silane coupling agent is obtained;
[0009] Step 3, adding 0.2-0.5 parts of Pebax-1657 and 6.47-10 parts of ethanol into a flask, and heating the flask in an oil bath at 85-95° C. for 6-12 hours to obtain a Pebax solution of uniform concentration;
[0010] Step 4, adding the nano ZSM-5 modified by the silane coupling agent as a filler into anhydrous ethanol, ultrasonicating for 2 to 6 hours, and then placing it on a stirring table and stirring for 24 to 72 hours to obtain a nano ZSM-5 filler casting solution modified by the silane coupling agent;
[0011] Step 5, weigh 6 to 7 parts of Pebax-1657 solution into a reagent bottle, and drop 0.2 to 1.5 parts of silane coupling agent modified nano ZSM-5 filler casting solution therein, oscillate using a turbine oscillator for 120 to 240 minutes and ultrasonically treat for 15 to 30 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed, and the prepared mixed matrix membrane solution is poured onto a polytetrafluoroethylene plate, placed in a constant temperature oven at 60 to 80°C and dried for 18 to 24 hours, and then placed in a vacuum oven at 60 to 80°C and vacuumed to continue to remove the solvent for 18 to 30 hours to obtain a mixed matrix membrane of nano ZSM-5 modified by a silane coupling agent.
[0012] Furthermore, the mass ratio of ethanol to water in step 3 is 6-10:1-4.
[0013] Furthermore, the rotation speed of the centrifuge used in step 1 is 7000-12000 rpm, and the centrifugation time is 5-15 min.
[0014] Furthermore, in step 4, the content of the nano ZSM-5 modified by the silane coupling agent in the nano ZSM-5 filler casting solution modified by the silane coupling agent is 1% to 4%.
[0015] Furthermore, the thickness of the mixed matrix membrane of nano ZSM-5 modified by the silane coupling agent in step 5 is 30 to 70 μm.
[0016] Furthermore, the ultrasonic stirring and mixing method in step 4 is stirring at a speed of 300-600 rpm at room temperature for 30-60 minutes, followed by ultrasonic dispersion for 15-45 minutes.
[0017] Furthermore, the crystallization temperature of the electric constant temperature blast drying oven in step 1 is 120-150° C. and the time is 4-16 hours.
[0018] Furthermore, the drying temperature in step 2 is 60 to 90° C. and the drying time is 12 to 36 hours.
[0019] Furthermore, according to the method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane according to any one of claims 1 to 8, the mixed matrix membrane prepared by the present invention is used for CO2 / N2 gas separation.
[0020] Based on the above technical solution, the mixed matrix membrane prepared by the present invention is used for CO2 / N2 gas separation.
[0021] The structural formulas of the above-mentioned substances are as follows:
[0022] The structural formula of ZSM-5 is:
[0023]
[0024] The structural formula of 3-aminopropyltriethoxysilane (APTES) is:
[0025]
[0026] The structural formula of β-CD (β-CD) is:
[0027]
[0028] The structural formula of pebax-1657 is:
[0029]
[0030] The invention uses pebax-1657 as a matrix material and nano ZSM-5 modified by 3-aminopropyltriethoxysilane as a silane coupling agent as a filler to prepare a mixed matrix membrane.
[0031] First, it has excellent mechanical properties. Pebax is a block copolymer formed by blending polyether segments (PE) and amide segments (PA); the polyether segments exhibit rubbery properties, ensuring that the membrane material itself has a high free volume fraction, which can provide a good gas transmission channel and reduce mass transfer resistance; at the same time, the large number of basic amine groups in the polyether front amide have a strong interaction ability with CO2, which can increase the solubility of CO2 in the membrane, thereby effectively improving the membrane material's solubility selectivity for CO2 gas.
[0032] Secondly, the introduction of porous nano ZSM-5 filler significantly improves the performance of the membrane. It is synthesized by tetrapropylammonium hydroxide template, which makes the organic molecules and inorganic skeletons have a very compact fit. At the same time, the organic structure directing agent has only one orientation in the pore or cage, and cannot move freely to create a porous filler with a suitable pore size structure. This provides a transmission channel for CO2 in the membrane, which helps the effective permeation of CO2 and thus improves the mass transfer efficiency of the membrane. At the same time, the strong acid sites and catalytic activity of ZSM-5 provide additional functions for the gas separation process. Porous nano ZSM-5 also improves the mechanical and thermal stability of the membrane, enabling it to maintain performance under more stringent operating conditions, while enhancing the membrane's anti-pollution ability, reducing the accumulation of pollutants on the membrane surface, and extending the service life of the membrane. The combined effect of these characteristics makes it a key component to improve the performance of mixed matrix membranes, especially in the field of gas separation, it can effectively improve the selectivity and permeability of the membrane to specific gases, and meet the demand for high-purity gases in industrial applications.
[0033] Finally, the siloxane groups in 3-aminopropyltriethoxysilane can undergo condensation reaction with the hydroxyl groups on the surface of nano ZSM-5 to form stable chemical bonds, thereby enhancing the structural stability of nano ZSM-5. The amino and other functional groups on the surface of nano ZSM-5 modified with silane coupling agents can increase its adsorption capacity for specific substances. The amino groups of 3-aminopropyltriethoxysilane can form hydrogen bonds or chemical bonds with the organic polymer chains, thereby improving the dispersibility of porous nano ZSM-5 in organic polymers.
[0034] The nano ZSM-5 mixed matrix membrane modified with a silane coupling agent prepared by the present invention is compared with a nano ZSM-5 mixed matrix membrane modified with β-cyclodextrin (β-CD) which also has abundant CO2-philic groups, further illustrating the excellent permeability and high CO2 / N2 selectivity of the nano ZSM-5 mixed matrix membrane modified with a silane coupling agent.
[0035] Through testing, the mixed matrix membrane prepared with nano ZSM-5 as filler has CO2 permeability PCO2=77.28Barrer, CO2 / N2 is 71.08, the mixed matrix membrane prepared with β-CD modified nano ZSM-5 as filler has CO2 permeability PCO2=82.59Barrer, and CO2 / N2 selectivity reaches 78.23, while the mixed matrix membrane prepared with silane coupling agent modified nano ZSM-5 as filler has CO2 permeability PCO2=110.96Barrer, CO2 / N2 selectivity reaches up to 87.56, which significantly improves the gas permeability and selectivity, making the nano ZSM-5-based mixed matrix membrane modified by silane coupling agent show great application potential in the industrial gas separation process, especially in improving CO2 capture and separation efficiency. This membrane can not only effectively promote the permeation of CO2, but also increase the permeation of CO2 while maintaining high CO2 / N2 selectivity, which is of great significance for reducing greenhouse gas emissions, improving energy efficiency and achieving environmental sustainable development. In addition, this performance advantage also shows the key role of silane coupling agents in improving the interfacial compatibility between nanofillers and polymer matrices, and by enhancing the interaction between the two, the overall performance and stability of the membrane are improved. Therefore, silane coupling agent-modified nano ZSM-5 fillers provide a new strategy for the design and preparation of mixed matrix membranes, which is expected to be widely used and further studied in the field of gas separation technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a scanning electron microscope image of the nano ZSM-5 modified with a silane coupling agent prepared in Example 1;
[0037] Figure 2 The X-ray diffraction patterns of ZSM-5 prepared in Example 1 and Comparative Examples 2 to 5;
[0038] Figure 3 X-ray diffraction patterns of the mixed matrix membranes prepared in Examples 1 to 4 and Comparative Example 1;
[0039] Figure 4 The performance diagram of the mixed matrix membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0040] The technical solutions of the present invention are described below by listing some specific embodiments, but the protection scope of the present invention is not limited to the listed embodiments:
[0041] The materials used in the following examples were all purchased from the market, wherein Pebax-1657 was purchased from Arkema, France; toluene and amorphous silica were purchased from Tianjin Damao Chemical Reagent Co., Ltd.; ethanol, aluminum isopropoxide, tetrapropylammonium hydroxide (TPAOH), 3-aminopropyltriethoxysilane (APTES), and β-cyclodextrin (β-CD) were purchased from Aladdin Chemical Reagent Co., Ltd., USA.
[0042] Embodiment 1:
[0043] Step 1, by means of a steam-assisted method, 1 g of silica and 0.017 g of aluminum isopropoxide were weighed according to a silicon-aluminum ratio of Si:Al=200:1, stirred under the action of 0.7 mL of TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, 5 mL of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24 hours, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10 hours, centrifugal washing, blast drying oven drying, and calcined in a muffle furnace at 570°C to obtain nano ZSM-5;
[0044] Step 2, add 50mL toluene to beaker A, add 3mL APTES dropwise thereto, and allow APTES to fully diffuse in the toluene solution; add 50mL toluene to beaker B, then add 0.3136g of nano ZSM-5, and calculate according to the silicon content in ZSM-5 so that the silicon content in ZSM-5 and the silicon content in APTES are 1:1.5, and drop the solution in beaker A into beaker B. The speed of this process is 800r / min, and stirring is continued for 2 hours. Then, the mixed solution is transferred to a round-bottom flask, 2 drops of ultrapure water are added, and the mixture is reacted in an oil bath at 80°C for 24h, and then centrifuged and washed with toluene and dried in a blast drying oven to finally obtain nano ZSM-5 modified with a silane coupling agent;
[0045] Step 3: Weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 and keep stirring at 85° C. for 6 hours to completely dissolve them, thereby obtaining a Pebax solution.
[0046] Step 4: Take 1 g of nano ZSM-5 modified with a silane coupling agent and put it in a glass bottle with a lid, add 20 mL of anhydrous ethanol, ultrasonicate for 2 h, and stir on a stirring table for 24 h to obtain a nano ZSM-5 filler casting solution modified with a silane coupling agent.
[0047] Step 5, take 6.70g of Pebax solution in a reagent bottle, add 0.2mL of silane coupling agent modified nano ZSM-5 filler casting solution thereto, oscillate with a turbine oscillator for 120min and ultrasonically treat for 30min, and then let it stand for 5min to obtain a 5wt.% mixed matrix membrane solution, pour the above mixed matrix membrane solution into a clean polytetrafluoroethylene mold, and then put the membrane into a constant temperature oven at 60°C and dry it for 24h, and finally continue to dry it in a vacuum oven for 24h to obtain a mixed matrix membrane of nano ZSM-5 modified by a silane coupling agent, and the thickness of the prepared mixed matrix membrane is 57-61μm.
[0048] The separation performance of the mixed matrix membrane was tested to be PCO2 = 87.62 Barrer, αCO2 / N2 = 80.21. It can be clearly seen that the gas permeability and gas selectivity of the mixed matrix membrane have been improved. Compared with the pure Pebax-1657 mixed matrix membrane, its CO2 permeation flux increased by 56.52%, and the CO2 / N2 selectivity increased by 101.89%; compared with the unmodified, its CO2 permeation flux increased by 13.38%, and the CO2 / N2 selectivity increased by 12.84%. Compared with the β-CD modified nano ZSM-5 mixed matrix membrane, its CO2 permeation flux increased by 6.09%, and the CO2 / N2 selectivity increased by 2.53%.
[0049] Figure 2 From the XRD spectrum of the nano ZSM-5 prepared in step 1, it can be seen that characteristic peaks appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, proving that the product prepared in step 1 has good crystallinity and is nano ZSM-5. Figure 1 This is a scanning electron microscope image of the nano ZSM-5 modified with a silane coupling agent prepared in step 2. It can be seen from the image that the nano ZSM-5 does not maintain the conventional morphology after being modified with a silane coupling agent, but still maintains good dispersibility. Figure 3The X-ray diffraction spectrum of the nano ZSM-5 mixed matrix membrane modified with silane coupling agent. Obvious diffraction peaks appeared at 2θ angles of 7.96°, 8.83°, 23.18°, 23.99° and 24.45° in the spectrum. The existence of these peaks confirmed that the nano ZSM-5 was successfully introduced into the system of the mixed matrix membrane, and proved that the modification treatment of the silane coupling agent did not damage the crystal structure of the nano ZSM-5, but effectively maintained its crystal characteristics. This result further verified that the silane coupling agent modification method can maintain the integrity of the nano ZSM-5 crystal while enhancing its interaction with the polymer matrix, thereby improving the overall performance of the mixed matrix membrane.
[0050] Embodiment 2:
[0051] Step 1, with the help of steam-assisted method, 1g of silica and 0.017g of aluminum isopropoxide were weighed according to the silicon-aluminum ratio Si:Al=200:1, stirred under the action of 0.7mL TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, 5mL of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24h, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10h, centrifugal washing, blast drying oven drying, and muffle furnace calcination to obtain nano ZSM-5;
[0052] Step 2, add 50mL toluene to beaker A, add 3mL APTES dropwise thereto, and allow APTES to fully diffuse in the toluene solution; add 50mL toluene to beaker B, then add 0.3136g of nano ZSM-5, and calculate according to the silicon content in ZSM-5 so that the silicon content in ZSM-5 and the silicon content in APTES are 1:1.5, and drop the solution in beaker A into beaker B. The speed of this process is 800r / min, and stirring is continued for 2 hours. Then, the mixed solution is transferred to a round-bottom flask, 2 drops of ultrapure water are added, and the mixture is reacted in an oil bath at 85°C for 24h, and then centrifuged and washed with toluene and dried in a blast drying oven to finally obtain nano ZSM-5 modified with a silane coupling agent;
[0053] Step 3, weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 thereto, keep stirring at 85° C. for 6 hours to completely dissolve them, and obtain a Pebax solution;
[0054] Step 4, take 1g of nano ZSM-5 modified with a silane coupling agent into a glass bottle with a lid, add 20mL of ethanol thereto, ultrasonicate for 2h, place on a stirring table and stir for 24h to obtain a nano ZSM-5 filler casting solution modified with a silane coupling agent;
[0055] Step 5: Take 6.70g of the Pebax solution obtained in step 3 into a reagent bottle, add 0.4mL of the silane coupling agent modified nano ZSM-5 filler casting solution prepared in step 4, oscillate with a turbine oscillator for 240min and ultrasonically treat for 30min, and then stand for 5min to obtain a 10wt.% mixed matrix membrane solution, pour the mixed matrix membrane solution into a clean polytetrafluoroethylene mold, and then put the membrane into a constant temperature oven at 60°C for 24h, and finally continue to dry in a vacuum oven for 24h to obtain a silane coupling agent modified nano ZSM-5 mixed matrix membrane. The thickness of the prepared mixed matrix membrane is 62-68μm.
[0056] The separation performance of the mixed matrix membrane was tested to be PCO2 = 110.96 Barrer, αCO2 / N2 = 87.56. It can be clearly seen that the gas permeability and gas selectivity of the mixed matrix membrane have been improved. Compared with pure Pebax-1657 mixed matrix membrane, its CO2 permeation flux increased by 98.21%, and CO2 / N2 selectivity increased by 120.39%; compared with the unmodified, its CO2 permeation flux increased by 43.58%, and CO2 / N2 selectivity increased by 23.19%; compared with β-CD modified nano ZSM-5 mixed matrix membrane, its CO2 permeation flux increased by 34.35%, and CO2 / N2 selectivity increased by 11.93%; at the same time, its performance broke through the 2008 Robbson upper limit.
[0057] Figure 3 The X-ray diffraction spectrum of the nano ZSM-5 mixed matrix membrane modified by the silane coupling agent. In the spectrum, there are obvious diffraction peaks at 7.96°, 8.83°, 23.18°, 23.99° and 24.45° at 2θ angles. The existence of these peaks confirms that the nano ZSM-5 is successfully introduced into the system of the mixed matrix membrane, and proves that the modification treatment of the silane coupling agent does not damage the crystal structure of the nano ZSM-5, but effectively maintains its crystal characteristics. This result further verifies that the silane coupling agent modification method can enhance its interaction with the polymer matrix while maintaining the integrity of the nano ZSM-5 crystal, thereby improving the overall performance of the mixed matrix membrane. In addition, the intensity of these characteristic peaks is enhanced compared to Example 1, which is due to the fact that the addition amount of the nano ZSM-5 modified by the silane coupling agent is higher than that of Example 1.
[0058] Embodiment 3:
[0059] Step 1, with the help of steam-assisted method, 1g of silica and 0.017g of aluminum isopropoxide were weighed according to the silicon-aluminum ratio Si:Al=200:1, stirred under the action of 0.7mL TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, 5mL of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24h, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10h, centrifugal washing, blast drying oven drying, and muffle furnace calcination to obtain nano ZSM-5;
[0060] Step 2, add 50mL toluene to beaker A, add 3mL APTES dropwise thereto, and make APTES fully diffuse in the toluene solution; add 50mL toluene to beaker B, then add 0.3136g nano ZSM-5, according to the silicon content in ZSM-5, so that the silicon content in ZSM-5 and the silicon content in APTES are 1:1.5, and the solution in beaker A is added dropwise to beaker B. The speed of this process is 800r / min, and stirring is continued for 2 hours, and then the mixed solution is transferred to a round-bottom flask, and then reacted in an oil bath at 85°C for 24h, and then centrifuged and washed with toluene, and dried in a blast drying oven, and finally the nano ZSM-5 modified with a silane coupling agent is obtained;
[0061] Step 3, weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 thereto, keep stirring at 85° C. for 6 hours to completely dissolve them, and obtain a Pebax solution;
[0062] Step 4, take 1g of nano ZSM-5 modified with a silane coupling agent into a glass bottle with a lid, add 20mL of ethanol thereto, ultrasonicate for 2h, place on a stirring table and stir for 24h to obtain a nano ZSM-5 filler casting solution modified with a silane coupling agent;
[0063] Step 5: Take 6.70g of the Pebax solution obtained in step 3 into a reagent bottle, add 0.6mL of the silane coupling agent modified nano ZSM-5 filler casting solution prepared in step 4, oscillate for 240min using a turbine oscillator and ultrasonically treat for 30min, and then stand for 5min to obtain a 15wt.% mixed matrix membrane solution, pour the mixed matrix membrane solution into a clean polytetrafluoroethylene mold, and then put the membrane into a constant temperature oven at 60°C for 24h, and finally continue to dry in a vacuum oven for 24h to obtain a silane coupling agent modified nano ZSM-5 mixed matrix membrane. The thickness of the prepared mixed matrix membrane is 59-68μm.
[0064] The separation performance of the mixed matrix membrane was tested to be PCO2 = 95.84 Barrer, αCO2 / N2 = 83.65. It can be clearly seen that the gas permeability and gas selectivity of the mixed matrix membrane have been improved. Compared with pure Pebax-1657 mixed matrix membrane, its CO2 permeation flux increased by 71.20%, and CO2 / N2 selectivity increased by 110.55%; compared with the unmodified, its CO2 permeation flux increased by 24.02%, and CO2 / N2 selectivity increased by 17.68%; compared with β-CD modified nano ZSM-5 mixed matrix membrane, its CO2 permeation flux increased by 16.04%, and CO2 / N2 selectivity increased by 6.93%.
[0065] Figure 3 The X-ray diffraction spectrum of the nano ZSM-5 mixed matrix membrane modified by the silane coupling agent. In the spectrum, there are obvious diffraction peaks at 7.96°, 8.83°, 23.18°, 23.99° and 24.45° at 2θ angles. The existence of these peaks confirms that the nano ZSM-5 is successfully introduced into the system of the mixed matrix membrane, and proves that the modification treatment of the silane coupling agent does not damage the crystal structure of the nano ZSM-5, but effectively maintains its crystal characteristics. This result further verifies that the silane coupling agent modification method can enhance its interaction with the polymer matrix while maintaining the integrity of the nano ZSM-5 crystal, thereby improving the overall performance of the mixed matrix membrane. In addition, the intensity of these characteristic peaks is enhanced compared to Example 2, which is due to the fact that the addition amount of the nano ZSM-5 modified by the silane coupling agent is higher than that of Example 2.
[0066] Embodiment 4:
[0067] Step 1, with the help of steam-assisted method, 1g of silica and 0.017g of aluminum isopropoxide were weighed according to the silicon-aluminum ratio Si:Al=200:1, stirred under the action of 0.7mL TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, 5mL of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24h, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10h, centrifugal washing, blast drying oven drying, and muffle furnace calcination to obtain nano ZSM-5;
[0068] Step 2, add 50mL toluene to beaker A, add 3mL APTES dropwise thereto, and allow APTES to fully diffuse in the toluene solution; add 50mL toluene to beaker B, then add 0.3136g of nano ZSM-5, and calculate according to the silicon content in ZSM-5 so that the silicon content in ZSM-5 and the silicon content in APTES are 1:1.5, and drop the solution in beaker A into beaker B. The speed of this process is 800r / min, and stirring is continued for 2 hours. Then, the mixed solution is transferred to a round-bottom flask, 2 drops of ultrapure water are added, and the mixture is reacted in an oil bath at 85°C for 24h, and then centrifuged and washed with toluene and dried in a blast drying oven to finally obtain nano ZSM-5 modified with a silane coupling agent;
[0069] Step 3, weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 thereto, keep stirring at 85° C. for 6 hours to completely dissolve them, and obtain a Pebax solution;
[0070] Step 4, take 1g of nano ZSM-5 modified with a silane coupling agent into a glass bottle with a lid, add 20mL of ethanol thereto, ultrasonicate for 2h, place on a stirring table and stir for 24h to obtain a nano ZSM-5 filler casting solution modified with a silane coupling agent;
[0071] Step 5: Take 6.70g of the Pebax solution obtained in step 3 into a reagent bottle, add 0.8mL of a silane coupling agent modified nano ZSM-5 filler casting solution, oscillate with a turbine oscillator for 240min and ultrasonically treat for 30min, and then stand for 5min to obtain a 20wt.% mixed matrix membrane solution, pour the mixed matrix membrane solution into a clean polytetrafluoroethylene mold, and then put the membrane into a constant temperature oven at 60°C for 24h, and finally continue to dry in a vacuum oven for 24h to obtain a silane coupling agent modified nano ZSM-5 mixed matrix membrane. The thickness of the prepared mixed matrix membrane is 61-67μm.
[0072] The separation performance of the mixed matrix membrane was tested to be PCO2 = 89.25 Barrer, αCO2 / N2 = 81.13. It can be clearly seen that the gas permeability and gas selectivity of the mixed matrix membrane have been improved. Compared with pure Pebax-1657 mixed matrix membrane, its CO2 permeation flux increased by 59.43%, and CO2 / N2 selectivity increased by 104.20%; compared with the unmodified, its CO2 permeation flux increased by 15.49%, and CO2 / N2 selectivity increased by 14.14%. Compared with β-CD modified nano ZSM-5 mixed matrix membrane, its CO2 permeation flux increased by 8.06%, and CO2 / N2 selectivity increased by 3.71%.
[0073] Figure 3 The X-ray diffraction spectrum of the nano ZSM-5 mixed matrix membrane modified by the silane coupling agent. In the spectrum, there are obvious diffraction peaks at 7.96°, 8.83°, 23.18°, 23.99° and 24.45° at 2θ angles. The existence of these peaks confirms that the nano ZSM-5 is successfully introduced into the system of the mixed matrix membrane, and proves that the modification treatment of the silane coupling agent does not damage the crystal structure of the nano ZSM-5, but effectively maintains its crystal characteristics. This result further verifies that the silane coupling agent modification method can enhance its interaction with the polymer matrix while maintaining the integrity of the nano ZSM-5 crystal, thereby improving the overall performance of the mixed matrix membrane. In addition, the intensity of these characteristic peaks is enhanced compared to Example 3, which is due to the fact that the addition amount of the nano ZSM-5 modified by the silane coupling agent is higher than that of Example 3.
[0074] Comparative Example 1:
[0075] Step 1, 0.2 g Pebax-1657 and 6.47 g ethanol were placed in a flask and placed in an oil bath at 85°C for 6 h to obtain a Pebax solution of uniform concentration;
[0076] Step 2: subject the above solution to ultrasonic degassing treatment, pour it into a polytetrafluoroethylene mold after standing, put it into a constant temperature oven at 60°C to dry for 24 hours, and then put it into a vacuum oven to evacuate and continue to remove the solvent for 24 hours to obtain a pure Pebax mixed matrix membrane.
[0077] The separation performance of pure Pebax-1657 mixed matrix membrane was tested to be PCO2=55.98 Barrer, αCO2 / N2=39.73.
[0078] Figure 3 The XRD spectrum of the pure Pebax-1657 mixed matrix membrane shows a broad diffraction peak at about 20°, which is mainly attributed to the diffraction of the PE crystal segment in Pebax, indicating that the Pebax-1657 polymer matrix itself has a lower crystalline structure and a higher amorphous region. This amorphous structure helps the diffusion of gas molecules in the membrane because they can pass more freely through the disordered polymer chains. In addition, this structural feature of the pure Pebax-1657 membrane also means that when fillers are introduced, such as nano ZSM-5, it may affect the crystallization behavior of the membrane, thereby affecting the gas separation performance of the membrane.
[0079] Comparative Example 2:
[0080] Step 1. With the help of a steam-assisted method, 1 g of silica and 0.017 g of aluminum isopropoxide were weighed according to the silicon-aluminum ratio Si:Al=200:1, and stirred under the action of 0.7 mL of TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, a small amount of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24 hours, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10 hours, centrifugal washing, blast drying oven drying, and calcined in a muffle furnace at 570°C to obtain dry ZSM-5 nanoparticles.
[0081] Step 2, add 1 g of the prepared ZSM-5 nanoparticles into 20 mL of ethanol, ultrasonicate for 2 h, and stir on a stirring table for more than 24 h to obtain a ZSM-5 casting solution;
[0082] Step 3, weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 thereto, keep stirring at 85° C. for 6 hours to completely dissolve them, and obtain a Pebax solution;
[0083] Step 4, weigh 6.70g of the Pebax solution obtained in step 2 into a reagent bottle, and drop 0.2mL of the ZSM-5 casting solution prepared in step 2 therein, oscillate using a turbine oscillator for 120-240min and ultrasonically treat for 15-30min, after the filler and the polymer solution are evenly mixed, degas the 10wt.% mixed matrix membrane solution statically;
[0084] Step 5: Pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, place it in a 60°C constant temperature oven to dry for 24 hours, and then place it in a vacuum oven to evacuate and continue to remove the solvent for 24 hours to obtain a ZSM-5 / Pebax mixed matrix membrane. The prepared mixed matrix membrane has a thickness of 48 to 69 μm.
[0085] The separation performance of ZSM-5@Pebax-1657 mixed matrix membrane was tested to be PCO2=77.28 Barrer, αCO2 / N2=71.08.
[0086] Figure 2 From the XRD spectrum of the nano ZSM-5 prepared in step 1, it can be seen that characteristic peaks appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, proving that the product prepared in step 1 has good crystallinity and is nano ZSM-5.
[0087] Comparative Example 3:
[0088] Step 1, by means of a steam-assisted method, 1 g of silica and 0.017 g of aluminum isopropoxide were weighed according to a silicon-aluminum ratio of Si:Al=200:1, stirred under the action of 0.7 mL of TPAOH until the aluminum isopropoxide was fully dissolved, and then silica was added, transferred to an open glass bottle, and then the open glass bottle was transferred to a polytetrafluoroethylene bottle, a small amount of deionized water was added between the two, and then transferred to a reactor, aged at room temperature for 24 hours, and then the reactor was transferred to a 135°C electric constant temperature blast drying oven for reaction for 10 hours, centrifugal washing, blast drying oven drying, and muffle furnace calcination to obtain dry ZSM-5 nanoparticles;
[0089] Step 2, the molar amount of ZSM-5: the molar amount of β-CD = 1:1.2, add 50mL of toluene to beaker A, then add 2mL of β-CD dropwise to promote the full diffusion of β-CD in the toluene solution, then add 50mL of toluene to beaker B, then add 0.3675g of pure ZSM-5 nanoparticles obtained in step 1, stir beakers A and B vigorously for 2h, then transfer to a round-bottom flask, add two drops of ultrapure water, and then react in an oil bath at 90°C for 24h, then filter, wash and dry with toluene to finally obtain β-CD modified nano ZSM-5;
[0090] Step 3, weigh 22.85 g of ethanol and 9.79 g of distilled water, mix them, heat them to 85° C. under stirring, then add 1.01 g of Pebax-1657 thereto, keep stirring at 85° C. for 6 hours to completely dissolve them, and obtain a Pebax solution;
[0091] Step 4, taking 1 g of the β-CD modified nano ZSM-5 nanoparticles obtained in step 2 into a glass bottle with a lid, adding 20 mL of ethanol thereto, ultrasonicating for 2 h, and then placing on a stirring table and stirring for 24 h to obtain a β-CD modified nano ZSM-5 casting solution;
[0092] Step 5, taking 6.70 g of the Pebax solution obtained in step 3 into a reagent bottle, adding 0.4 mL of the β-CD modified nano ZSM-5 casting solution prepared in step 4, oscillating for 120 min using a turbine oscillator and ultrasonically treating for 15 min, and then standing for 5 min to obtain a 10 wt.% mixed matrix membrane solution;
[0093] Step 6: Pour the above mixed matrix membrane solution into a clean polytetrafluoroethylene mold, then place the membrane in a constant temperature oven at 60°C and dry it for 24 hours, and finally continue to dry it in a vacuum oven for 24 hours to obtain a β-CD modified nano ZSM-5 mixed matrix membrane. The thickness of the prepared mixed matrix membrane is 57 to 66 μm.
[0094] The separation performance of the tested β-CD modified nano ZSM-5 mixed matrix membrane was PCO2=82.59 Barrer, αCO2 / N2=78.23.
[0095] Figure 2 From the XRD spectrum of the nano ZSM-5 prepared in step 1, it can be seen that characteristic peaks appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, proving that the product prepared in step 1 has good crystallinity and is nano ZSM-5.
[0096] Comparative Example 4:
[0097] Synthesis of ZSM-5 using APTES and TPAOH as dual templates:
[0098] Step 1, mix 0.7 mL of TPAOH and 1.5 mL of APTES;
[0099] Step 2, weigh 0.017 g of aluminum isopropoxide, mix it with the mixed solution obtained in step 1, and stir it thoroughly to dissolve it;
[0100] Step 3, weigh 1.01 g of silicon dioxide, mix it with the mixed solution obtained in step 2, and stir it thoroughly;
[0101] Step 4, transfer it to a reactor, age it at room temperature for 24 hours, and then transfer the reactor to a 130°C oven for reaction for 4 hours;
[0102] Step 5, washing by centrifugation 3 times with deionized water, and then drying in a 60°C forced air drying oven;
[0103] Step 6: Grind the dried sample using a mortar and then calcine it in a muffle furnace at 570° C. to remove excess template.
[0104] like Figure 2 As shown in the XRD spectrum, no characteristic peaks appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, but a broad, diffusely scattered peak appears. This indicates that the atomic arrangement of the measured sample lacks long-range order, presents typical amorphous structural characteristics, and the product is not crystallized.
[0105] Comparative Example 5:
[0106] Synthesis of ZSM-5 using β-CD and TPAOH as dual templates:
[0107] Step 1, mix 1 mL of TPAOH and 1.5 mL of β-CD;
[0108] Step 2, weigh 0.017 g of aluminum isopropoxide, mix it with the mixed solution obtained in step 1, and stir it thoroughly to dissolve it;
[0109] Step 3, weigh 1.01 g of silicon dioxide, mix it with the mixed solution obtained in step 2, and stir it thoroughly;
[0110] Step 4, transfer it to a reactor, age it at room temperature for 24 hours, and then transfer the reactor to a 130°C oven for reaction for 4 hours;
[0111] Step 5, washing by centrifugation 3 times with deionized water, and then drying in a 60°C forced air drying oven;
[0112] Step 6: Grind the dried sample using a mortar and then calcine it in a muffle furnace at 570° C. to remove excess template.
[0113] like Figure 2 As shown in the XRD spectrum, no characteristic peaks appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, but a broad, diffusely scattered peak appears. This indicates that the atomic arrangement of the measured sample lacks long-range order, presents typical amorphous structural characteristics, and the product is not crystallized.
[0114] Figure 4 This is a performance diagram of the mixed matrix membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3. As shown in the figure, the gas permeability and gas selectivity of the mixed matrix membranes of Examples 1 to 4 are generally higher than those of Comparative Examples 1 to 3, and Example 2 has the best gas permeability and gas selectivity, and its performance has exceeded the Robbson upper limit in 2008 (black line in the figure).
[0115] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane, characterized in that: The following steps are involved: Step 1, weighing 1-1.5 parts of aluminum isopropoxide and dissolving it in 48-80 parts of an organic template, stirring until the aluminum isopropoxide is fully dissolved, adding 52-65 parts of silicon dioxide, stirring evenly to obtain a slightly wet gel-like mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding deionized water outside the glass bottle mouth in the lining, aging the encapsulated hydrothermal reactor at room temperature for 24-72 hours, transferring the hydrothermal reactor to an electric constant temperature blast drying oven for crystallization treatment to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain dry nano ZSM-5; Step 2, add 50-150 parts of toluene to beaker A, add 1-5 parts of 3-aminopropyltriethoxysilane dropwise thereto, and fully dissolve it in the toluene solution; add 50-150 parts of toluene to beaker B, then add 0.05-1 part of nano ZSM-5, and drop the solution in beaker A into beaker B. The speed of this process is 800r / min, and then continue to stir for 2-5 hours, then transfer the mixed solution to a round-bottom flask, add 1-5 drops of ultrapure water, and react in an oil bath at 80-90°C for 12-36 hours. After centrifugal washing and drying with toluene, nano ZSM-5 modified with a silane coupling agent is obtained; Step 3, adding 0.2-0.5 parts of Pebax-1657 and 6.47-10 parts of ethanol into a flask, and heating the flask in an oil bath at 85-95° C. for 6-12 hours to obtain a Pebax solution of uniform concentration; Step 4, adding the nano ZSM-5 modified by the silane coupling agent as a filler into anhydrous ethanol, ultrasonicating for 2 to 6 hours, and then placing it on a stirring table and stirring for 24 to 72 hours to obtain a nano ZSM-5 filler casting solution modified by the silane coupling agent; Step 5, weigh 6 to 7 parts of Pebax-1657 solution into a reagent bottle, and drop 0.2 to 1.5 parts of silane coupling agent modified nano ZSM-5 filler casting solution therein, oscillate using a turbine oscillator for 120 to 240 minutes and ultrasonically treat for 15 to 30 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed, and the prepared mixed matrix membrane solution is poured onto a polytetrafluoroethylene plate, placed in a constant temperature oven at 60 to 80°C and dried for 18 to 24 hours, and then placed in a vacuum oven at 60 to 80°C and vacuumed to continue to remove the solvent for 18 to 30 hours to obtain a mixed matrix membrane of nano ZSM-5 modified by a silane coupling agent.
2. The method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The mass ratio of ethanol to water in step 3 is 6-10:1-4.
3. The method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The centrifuge used in step 1 has a rotation speed of 7000-12000 rpm and a centrifugation time of 5-15 min.
4. The method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The content of the nano ZSM-5 modified by the silane coupling agent in the nano ZSM-5 filler casting solution modified by the silane coupling agent in step 4 is 1% to 4%.
5. The method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: In step 5, the thickness of the mixed matrix membrane of nano ZSM-5 modified by the silane coupling agent is 30 to 70 μm.
6. The method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The ultrasonic stirring and mixing method in step 4 is to stir at a speed of 300-600 rpm for 30-60 minutes at room temperature, and then ultrasonically disperse for 15-45 minutes.
7. The method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The crystallization temperature of the electric constant temperature blast drying oven in step 1 is 120-150° C. and the time is 4-16 hours.
8. The method for preparing a silane coupling agent-modified nano ZSM-5 mixed matrix membrane according to claim 1, characterized in that: The drying temperature in step 2 is 60 to 90° C. and the drying time is 12 to 36 hours.
9. The method for preparing a silane coupling agent modified nano ZSM-5 mixed matrix membrane according to any one of claims 1 to 8, characterized in that: The mixed matrix membrane prepared by the invention is used for CO2 / N2 gas separation.
Citation Information
Patent Citations
ZSM-5 molecular sieve filled silicon rubber / cellulose acetate composite membrane and preparation method thereof
CN101816897A
Preparation method of SAPO-34 / PDMS gas permeable membrane
CN111482092A
Method for improving CO2 separation performance of mixed matrix membrane by using gamma-cyclodextrin
CN115624843A
Method for improving CO2 separation performance of mixed matrix membrane by utilizing topological molecular sieve (ZSM-5)
CN118105853A
Cited By
Silane modified MXene nanosheet mixed matrix membrane and application thereof in O2 / N2 gas separation
CN121222280A